Recent Advancement of Ullmann Condensation Coupling Reaction in the Formation of Aryl-Oxygen (C-O) Bonding by Copper-Mediated Catalyst - Choong Jian Fui; Mohd Sani Sarjadi; Shaheen M. Sarkar; Md Lutfor Rahman (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Transition metal-catalyzed chemical transformation of organic electrophiles and organometallic reagents belong to the most important cross coupling reaction in organic synthesis. The biaryl ether division is not only popular in natural products and synthetic pharmaceuticals but also widely found in many pesticides, polymers, and ligands. Copper catalyst has received great attention owing to the low toxicity and low cost. However, traditional Ullmann-type couplings suffer from limited substrate scopes and harsh reaction conditions. The introduction of homogeneous copper catalyst with presence of bidentate ligands over the past two decades has totally changed this situation as these ligands enable the reaction promoted in mild condition. The reaction scope has also been greatly expanded, rendering this copper-based cross-coupling attractive for both academia and industry. In this review, we will highlight the latest progress in the development of useful homogeneous copper catalyst with presence of ligand and heterogeneous copper catalyst in Ullmann type C-O cross-coupling reaction. Additionally, the application of Ullmann type C-O cross coupling reaction will be discussed.